Civic programmatic participation in public health: the case of Argentina - Tulia G. Falleti; Santiago L. Cunial
Abstract: Since the Alma Ata World Health Organization Conference in 1978, countries around the world have adopted institutions that promote the participation of citizens in their public health systems. The main objectives of this article are two-fold. First, we describe the origins and implementation of a national-level civic participatory program that was in place in Argentina in the mid-2000s: the Local Participatory Projects (Proyectos Locales Participativos). Second, we analyze the 201 local participatory projects that were carried out in Argentina between 2007 and 2008. We study health and environmental problems that prompt people's participation in the program and the social dynamics through which such participation is executed.